CATALPA L. TURKUMI TURLARINI INTRODUKSION BAHOLASh NATIJALARI - Dosjanova, G.D.; Tursunboev, H.E.; Urgenichbayev, A.A.; Jumagalieva, R.K.; Ochilov, U.A. (SCIENCE and SOCIETY, 2025)
For the first time in this article, the results of an intraductive assessment of the Catalpa species in the conditions of Karakalpakstan were studied. Based on the scientific results obtained, scientific data on the level of prospects of Catalpa bignonioides, catalpa speciosa and catalpa ovata species under the conditions of introduction are presented.
Keywords: Catalpa; introduction; level of foresight; branching; vegetative; generative; stem